2022
DOI: 10.3390/v14112566
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type Variability in the Incorporation of Lipids in the Dengue Virus Virion

Abstract: A lipid bilayer produced from the host membrane makes up around 20% of the weight of the dengue virus (DENV) virion and is crucial for virus entry. Despite its significance, the virion’s lipid composition is still poorly understood. In tandem with lipid profiles of the cells utilised to generate the virions, this work determined a partial lipid profile of DENV virions derived from two cell lines (C6/36 and LLC-MK2). The results showed distinctive profiles between the two cell types. In the mammalian LLC-MK2 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…DENV envelop contains lipids, which composition partially varies when viruses derive from mosquito or mammalian cells 57,58 . To evaluate the impact of DENV-lipids on DENV infection, we produced DENV in mosquito and monkey cells, and isolated virions from EVs 59 using discontinuous sucrose density gradient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DENV envelop contains lipids, which composition partially varies when viruses derive from mosquito or mammalian cells 57,58 . To evaluate the impact of DENV-lipids on DENV infection, we produced DENV in mosquito and monkey cells, and isolated virions from EVs 59 using discontinuous sucrose density gradient.…”
Section: Resultsmentioning
confidence: 99%
“…In support of a specific function for mosquito EVlipids, human EV-lipids did not influence DENV infection (Figure 1E), nor cell viability (Figure S4D). DENV envelop contains lipids, which composition partially varies when viruses derive from mosquito or mammalian cells 57,58 . To evaluate the impact of DENV-lipids on DENV infection, we produced DENV in mosquito and monkey cells, and isolated virions from EVs 59 using discontinuous sucrose density gradient.…”
Section: Mosquito Ev-lipids and Neither Human Ev-lipids Nor Virion Li...mentioning
confidence: 99%
“…To evaluate the virucidal disinfectant activity, we used two enveloped viruses, which differ in the lipid content [ 30 , 31 ] and protein structure [ 24 , 26 ] that comprise the viral envelope. The results indicated that DENV-2 was more sensitive to the action of test solutions than CHIKV.…”
Section: Discussionmentioning
confidence: 99%
“…LDs are thought to have conflicting roles in viral infection: many reports have demonstrated that enveloped viruses usurp LDs and alter lipidomic profiles of host cells to enhance their viral life cycles, with lipids accounting for 20-30% of the weight of the virion 62,67,[79][80][81][82][83] . DENV infection, for example, increases LD formation 62 , recruiting FAS to the virus replication site 65 , and its capsid protein accumulates on the surface of LDs, facilitating viral replication by providing a platform for nucleocapsid formation during encapsidation 67 .…”
Section: Discussionmentioning
confidence: 99%